Serum zinc and manganese levels in subjects with type 2 diabetes mellitus - Eva, Hossneara; Akhter, Quzi Shamima; Alam, Md Khairul (Journal of Bangladesh Society of Physiologist, 2016)
Background: Serum level of several trace elements such as zinc (Zn) and manganese (Mn) levels are altered in type 2 DM and its deficiencies are associated with the development of microvascular and macrovascular complications. Objective: To assess the serum zinc (Zn) and manganese (Mn) levels in subjects with type 2 diabetes mellitus. Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from July 2014 to June 2015. Fifty type 2 diabetic subjects with age ranging from 40 to 55 years of both sexes were study group and 50 age, sex and BMI matched healthy subjects were control group. Patients were selected from Bangladesh Institute of Research for Diabetic Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka. Serum Zn and Mn levels were estimated by flame atomic absorption spectrophotometry. For statistical analysis, unpaired Studentst test and chi square test was performed. Results: In this study, mean serum zinc and manganese levels were significantly (P<0.001) lower in the study group than that of control group. In addition, hypozincemia in 36% and hypomanganesemia in 18% of diabetic patients were observed and which was significantly (p<0.001) higher than those of control. Conclusion: From this study, it may be concluded that serum zinc and manganese deficiencies may develop as diabetes related complications. Bangladesh Soc Physiol. 2016, December; 11(2): 50-53